Multilateral sanctions revisited : lessons learned from Margaret Doxey - Charron, Andrea; Portela, Clara (McGill-Queen's/Brian Mulroney Institute of Government studies in leadership, public policy, and governance ;, 2022)
"Sanctions are "back with a vengeance" with new objectives, measures, challenges, and opportunities. Shaping the thinking of generations of scholars, Canadian visionary Margaret Doxey anticipated and analyzed these issues, making now the time to rediscover her seminal lessons and apply them to emerging sanctions practices that are taking shape in an increasingly geopolitically-contested environment. Written by an international, all-female team of authors, Multilateral Sanctions Revisited explores UN measures, regional sanctions, and autonomous measures and their interrelations. Informed by Margaret Doxey's insights, the authors trace the evolution of scholarship surrounding multilateral sanctions. The first section analyzes how different actors, such as great powers and regional organizations, employ multilateral sanctions. Turning to contemporary issues, the book's second section addresses the application and consequences of multilateral sanctions including the norms they enforce, the pernicious problem of evasion, and future challenges, such as sanctioning cryptocurrencies. Multilateral Sanctions Revisited is both a reference source for academics and a guidebook for practitioners written by leading and emerging sanctions scholars from three different continents."--